Initial experience with indium-111 autologous leucocyte imaging in patients with acute pancreatitis. Issue 6393 (3rd September 1983) - Anderson, J R; Spence, R A; Laird, J D; Ferguson, W R; Kennedy, T L
Abstract : Indium-111 labelled autologous leucocyte imaging was used to assess severity in 13 patients with acute pancreatitis. All three patients with severe disease as judged by a prognostic factor grading system had a positive result on imaging. A fourth patient with mild disease as judged by prognostic factors had a positive imaging result and 14 days later developed a pseudocyst. There were no false positive or false negative scans. Evidence from three patients suggested that a positive 111In-leucocyte imaging result implies substantial fat necrosis. In this study imaging was as accurate as prognostic factor grading. The technique may be a useful method of separating mild from severe acute pancreatitis.